DETERMINANTS OF BANK PROFITABILITY: A NEW EVIDENCE FROM STATE-OWNED BANKS IN INDONESIA - Prasanto, Ovy; Wulandari, Dwi; Narmaditya, Bagus Shandy; Kamaludin, Mahirah (TRIKONOMIKA, 2020)
This paper investigates the factors that determine bank profitability in Indonesia particularly on state-owned banks during the 2007 to 2017. The research applied Vector Error Correction Model (VECM) to measure short-term and long-term effects of independent variable on dependent variable. The research data ini this paper is drawn from two main sources namely Bank Indonesia (BI) and Financial Services Authority (OJK) from 2007 to 2017. The findings showed that in the long term, BOPO, LDR, NPLs, economic growth, and exchange rates have positive relationship toward bank profitability while in the short term, inflation and BI rates do not have effect on bank profitability. However, in the short run, all variables mentioned do not have impact toward banking profitability. In addition, based on Impulse Response Function test, it showed that there are only two independent variables are able to provide a response in case of shock, namely inflation and the exchange rate toward bank’s profitability.